Analysis Company Value based Good Corporate Governance on Financial Performance in the Service Trade and Investment Sector on the Indonesian Stock Exchange 2020-2022 - Azaluddin Azaluddin (Sang Pencerah: Jurnal Ilmiah Universitas Muhammadiyah Buton, 2023)
The purpose of this study was to examine the effect of financial performance, as measured by return on equity (ROE), on firm value by including good corporate governance (GCG) as a moderator. The study used a sample of eight companies listed on the Indonesia Stock Exchange (IDX). Information about company revenues, one of the information included in financial reports, is used as a focal point because information about company revenues can be used to assess management performance and responsibilities with a total of 32 observations. The data collection method used in this study reads, records and records monthly reports for 2021-2022 related to downloading data and information on companies in the trade, services and investment sectors listed on the Indonesian Stock Exchange. The results of this study indicate that financial performance has a positive impact on goodwill. The results of this study indicate that the value of Indonesian companies, especially those engaged in the trade and investment services sector, is determined by the earning power of company assets, and the higher the earning power, the more efficient the turnover of assets and funds is displayed.